Dampak Belanja Bantuan Operasional Perguruan Tinggi Negeri, Rupiah Murni dan Penerimaan Negara Bukan Pajak Terhadap Akreditasi Program Studi - Akidah Fitrah; Dodik Juliardi (Owner : Riset dan Jurnal Akuntansi, 2023)
Accreditation of current study programs as part of the quality of education, on the one hand, the higher education budget being disbursed by the government is getting bigger. The purpose of this study was to empirically examine the effect of State University Operational Assistance spending, Pure Rupiah spending and Non-Tax State Revenue spending on the Accreditation of State University A/Excellent Study Programs in Indonesia. This research is a causal research with a quantitative approach. The population in this study are State Universities under the Ministry of Education, Culture, Research and Technology. The sampling technique used purposive sampling. The data used is secondary data in the form of performance reports. The data analysis technique used is panel data regression. The results of the study show that in terms of State University Operational Assistance Expenditures, Pure Rupiah Expenditures and Non-Tax State Revenue Expenditure simultaneously affect Study Program Accreditation. Partially, State University Operational Assistance Expenditures have a positive and insignificant effect on State University A/Excellent Study Program Accreditation. Pure Rupiah spending has a positive and significant effect on Accreditation of A/Excellent Study Programs in State Universities. Expenditures of Non-Tax State Revenue have a negative and significant effect on the Accreditation of State Higher Education A/Excellent Study Programs